New Zealand students' test-taking motivation: an experimental study examining the effects of stakes. Issue 4 (4th July 2022) - Zhao, Anran; Brown, Gavin T. L.; Meissel, Kane
ABSTRACT: Students' test-taking motivation confounds test performance. This study examines students' conceptions of tests and test-taking motivation when different test consequences are at play. In a between-subjects experimental design, a sample of 479 New Zealand senior secondary school students were randomly assigned to one of the three vignette consequence conditions (i.e. none, country or self). Students self-reported conceptions of tests and test-taking motivation which were analysed with confirmatory factor analysis, structural equation modelling and latent mean analyses across test-consequence conditions. Students' general belief about tests was a positive indicator of their perceived effort expenditure ( β = .25). Both effort and anxiety increased significantly as consequence increased by medium-to-large effect size (ranges between 0.42 and 1.30). Effort and motivation were notably lower when the country was at stake versus the self at stake condition, raising doubts about the validity of New Zealand rankings in international large-scale assessments.